2000
DOI: 10.1159/000020202
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Radical Prostatectomy: Preliminary Results

Abstract: Background: Retropubic and perineal radical prostatectomy are used for curative treatment of localized prostate cancer. More complex urological procedures are now being done with laparoscopy. We present our initial results of transperitoneal laparoscopic radical prostatectomy.Materials and Methods: Twenty laparoscopic radical prostatectomies were performed between May 1998 and May 1999. The mean age at the time of surgery was 64.2 years. There were 14 stage T1c, 5 stage T2a and 1 stage T2b tumors. The preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
1
11

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 13 publications
(17 reference statements)
8
31
1
11
Order By: Relevance
“…Rassweiler et al [9] reported a rate of positive surgical margins in pT2 tumours of 2.3%, in pT3a of 15% and in pT3b of 34%. These results compare with those of other smaller series [14]. In our experience with EERPE the rate of positive surgical margins for pT2 tumours was 6.1% and for pT3 29.4% [13].…”
Section: The Results Of Lrp and Eerpsupporting
confidence: 76%
“…Rassweiler et al [9] reported a rate of positive surgical margins in pT2 tumours of 2.3%, in pT3a of 15% and in pT3b of 34%. These results compare with those of other smaller series [14]. In our experience with EERPE the rate of positive surgical margins for pT2 tumours was 6.1% and for pT3 29.4% [13].…”
Section: The Results Of Lrp and Eerpsupporting
confidence: 76%
“…Recently, they presented their experience with 260 cases [14]. Another Paris group reported about their success of laparoscopic radical prostatectomy in 20 patients [4]. At first, we oriented ourselves by the technique described by Guillonneau and Vallancien with the aim of verifing its feasibility and its possible use a standardized procedure.…”
Section: Discussionmentioning
confidence: 99%
“…After they had to convert to open surgery in 7 patients initially, this was in no case necessary after their 60th procedure. Abbou’s group [4]also reported a conversion rate of 0%. An important advantage of laparoscopic prostatectomy is the minimal blood loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, la serie inicial demostró resultados más bien desalentadores 3,4 . En el año 2000, los trabajos de Guillonneau y Vallancien demuestran por primera vez la factibilidad técnica de la prostatectomía radical laparoscópica, realizada por vía transperitoneal, con resultados aceptables y que han sido reproducidos en otros centros alrededor del mundo [5][6][7][8] . Con el propósito de imitar la vía extraperitoneal de la prostatectomía radical retropúbica, es que Bollens por primera vez describe esta técni-ca por una vía exclusiva preperitoneal, con buenos resultados 9 .…”
Section: Introductionunclassified